Job stress and organizational citizenship behavior among university teachers within Bangladesh: mediating influence of occupational commitment - Amint, Ruhul; Hossain, Alamgir; Masud, Abdullah Al (Zielona Góra: Faculty of Economics and Management Press)
This study aims to explore the impact of job stress on organizational citizenship behavior (OCB) among university teachers in Bangladesh along with the mediating effect of occupational commitment (OC) on this relationship. An online questionnaire survey using the Google form was conducted to collect data from respondents.
Keywords: job stress; occupational commitment; organization; citizenship behavior; university teacher; Bangladesh; stres w pracy; zaangażowanie zawodowe; organizacja; zachowanie obywatelskie; nauczyciel akademicki; Bangladesz